Anchoring of Cu (II)‐Schiff base complex on magnetic mesoporous silica nanoparticles: catalytic efficacy in one‐pot synthesis of 5‐substituted‐1H‐tetrazoles, antibacterial activity evaluation and immobilization of α‐amylase. (3rd March 2020) - Ahmadi, Ameneh; Sedaghat, Tahereh; Motamedi, Hossein; Azadi, Roya
Abstract: Magnetic mesoporous silica nanocomposite, Fe3 O4 @MCM‐41, was prepared and functionalized with N‐(2‐aminoethyl)‐3‐aminopropyltrimethoxysilane (AEAPS). Then Schiff base grafted nanoparticles were synthesized by the condensation of 5, 5'‐methylene bis (salicylaldehyde) and then benzhydrazide with Fe3 O4 @MCM‐41‐AEAPS. Finally, by adding Cu (CH3 COOH)2 .H2 O, the magnetic nanoparticles (MNPs) functionalized with Cu (II) Schiff base complex were synthesized. The new organic–inorganic hybrid nanocomposite was characterized by FT‐IR, PXRD, AAS, BET, TGA, VSM, FE‐SEM, HRTEM and EDX techniques. Then, the performance of this copper based magnetic nanocatalyst was investigated for the synthesis of 5‐substituted 1 H ‐tetrazole derivatives using one pot three‐component reactions of various aldehydes, hydroxyl amine hydrochloride and sodium azide. The catalyst can be easily isolated from the reaction mixture by applying an external magnet and reused for at least 5 times without significant loss in catalytic activity. Also, the antibacterial activity of the streptomycin loaded magnetic nanoparticles against Gram‐positive ( S. aureus ) and Gram‐negative ( E. coli ) bacteria in the presence and absence of a magnetic field were studied. Results revealed that when these materials exposed to the magnetic field, bacteriostatic activity of nanocomposites was increased. Furthermore, the enzyme immobilization ability of the synthesized compounds was investigated and the results showed that these nanoparticles efficiently immobilized amylase enzyme. Abstract : A new magnetic organic‐inorganic hybrid was synthesized. This nanocatalyst was investigated for synthesis of 5‐substituted 1H‐tetrazole derivatives. The magnetic mesoporous nanoparticles were evaluated for antibacterial activity and immobilization of enzyme.